COMMUNICATIVE SENTENCE TYPES AS MEANS OF EXPRESSINGOF AGREEMENT AND DISAGREEMENT (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This thesis explores how different communicative sentence types function as linguistic tools for expressing agreement and disagreement in English. The study examines declarative, interrogative, imperative, and exclamatory structures, analyzing their pragmatic roles in conversational interaction. Special attention is given to how sentence form influences politeness strategies, speaker attitude, and the degree of assertiveness in expressing consent or opposition. The findings highlight the importance of sentence type selection in maintaining effective communication, minimizing conflict, and ensuring clarity in dialogic exchanges.